The letters to the Colossians and to Philemon - Moo, Douglas J. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2024)
"The second edition of Douglas J. Moo's commentary on Colossians and Philemon"--
"A knowledgeable and evangelical guide to Paul's letters to the Colossians and to Philemon With brilliant exegesis and sound practical insight, noted commentator Douglas J. Moo explicates the Letters to the Colossians and to Philemon, with an eye toward their application for readers today. Moo bases his commentary on the Greek text of the letters, while accessibly explaining the English text to his contemporary audience. Freshly revised and updated, this second edition remains methodologically sound, authentically evangelical, and pastoral in approach. This invaluable volume of the Pillar New Testament Commentary series offers biblical insights to a wide range of readers, from teachers and students, to pastors and parishioners, to scholars and laypersons"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; RELIGION / Biblical Commentary / New Testament / Paul's Letters; RELIGION / Biblical Criticism & Interpretation / New Testament; Commentaries